Temporal Variability of Polycyclic Aromatic Hydrocarbons in Deep-Sea Cephalopods of the Northern Gulf of Mexico - Romero, Isabel C.; Judkins, Heather; Vecchione, Michael (Frontiers in Marine Science, 2020)
As part of the effort to understand the effects of the Deepwater Horizon Oil Spill (DWHOS), we analyzed tissue from five species of midwater oceanic cephalopods in the northern Gulf of Mexico (GoM) during three time periods, including one period sampled fortuitously just before the spill (2010), and two periods sampled after the spill (2011 and 2015-2016). The species, Japetella diaphana, Abralia redfieldi, Histioteuthis corona, Leachia atlantica, and Onychoteuthis banksii were collected in three geographic areas in the GoM (east, south and southeast of the Macondo wellhead). Results indicate a shift in the composition of polycyclic aromatic hydrocarbons (PAHs) in the tissue of all cephalopods after 2010, with a more petrogenic source in 2011 that weathered and mixed with other sources in 2015-2016. Overall, PAH concentrations, as well as lipid content, were lower in 2011 relative to 2010 and 2015-2016, suggesting secondary effects to oil-residues exposure from the DWHOS. Collectively, PAHs in the tissues of deep-sea cephalopods indicate an episodic exposure to petrogenic PAHs that occurred between 2010 (pre-spill) and 2011, and continued through 2015-2016.